2002
DOI: 10.1002/1521-3757(20020916)114:18<3618::aid-ange3618>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Monoanionic ligands of the type [R 2 P(E)NP(E)R 2 ] À 1 have been investigated extensively as ligands for both main group elements [1] and transition metals. [2] This widespread interest stems from their potential uses as lanthanide shift reagents, [2] industrial catalysts, [3] luminescent materials, [4] or in metal extraction processes. [5] Recently we [6] and Stahl et al. [7] reported the first ambidentate dianionic ligands [RN(E)P(m-NR) 2 P(E)NR] 2À 2, which adopt a variety of bonding modes, that is N,E, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
77
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 1 publication
4
77
0
Order By: Relevance
“…8,9 A fascinating feature of the chemistry of 1c is the 40 formation of the unusual ditelluride 2c upon stoichiometric oxidation of the sodium salt with iodine. 8,9 The ditelluride 2c may be considered to be the dimer of the tellurium-centered radical [TeP i Pr2N i Pr2PTe]…”
supporting
confidence: 73%
“…8,9 A fascinating feature of the chemistry of 1c is the 40 formation of the unusual ditelluride 2c upon stoichiometric oxidation of the sodium salt with iodine. 8,9 The ditelluride 2c may be considered to be the dimer of the tellurium-centered radical [TeP i Pr2N i Pr2PTe]…”
supporting
confidence: 73%
“…[Li(TMEDA)] 2 [tBuN(Te)P(-NtBu) 2 P(Te)NtBu)] was synthesized according to the literature procedure. [7] Spectroscopic methods NMR spectra were recorded using a JEOL DELTA EX 270 or a BRUKER Avance II 400 spectrometer. TMS was used as an internal standard for 1 H NMR.…”
Section: General Proceduresmentioning
confidence: 99%
“…[4] We have previously shown that the phosphorus-tellurium bond is stabilized by a negative charge in the anionic ligands {[R 2 P(Te)] 2 N} − [5] and we reported the X-ray structures of hexameric and tetrameric Ag(I) complexes of this ligand for R = iPr and Ph, respectively. [6] In a sequel to that work we have now investigated the reaction of the P-Te dianion [tBuN(Te)P(-NtBu) 2 P(Te)NtBu)] 2− (A) [7] with silver(I) iodide and found, unexpectedly, that a AgI complex of the neutral monotelluride ([tBu(H)N(Te)P(-NtBu) 2 PN(H)tBu]) (B) [8] is formed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] Although ditellurides of the type [R(Te)P(m-NtBu) 2 P(Te)R] (R ¼ Me, tBu) have been reported, [9] our attempts to oxidize tBuN(H)P(m-NtBu) 2 PN(H)tBu with an excess of elemental tellurium in boiling toluene produced only the monotelluride [tBuNH(Te)P(m-NtBu) 2 PN(H)tBu] in about 5 % yield. [10] Endeavors to generate (TePPh 2 ) 2 NH in a similar manner have also been unsuccessful. Consequently, we adopted a different approach to the synthesis of the anionic ligands 1 (E ¼ Te) and 2 (E ¼ Te), which involves metalation of the neutral imido or amido precursor prior to the reaction with tellurium.…”
mentioning
confidence: 99%